MANAGEMENT COMPETENCIES OF MANAGERS OF MICRO ENTERPRISES - Basumatary, Priyo; Hazarika, Balin (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Competency is a term used for specific skills to manage a certain assignment/work with proper knowledge and experience. Management competencies in similar way mean the ability to accomplish or manage certain assignment. Management competencies for management of a micro enterprise can be elaborated into production management competencies, financial management competencies and marketing management competencies. To run a business, a manager’s competency acts as a catalyst in their survival. Hence, a business is very much dependent on competencies of the manager. The present study aims to measure the management competencies required to run a micro business enterprise with reference to production, finance and marketing of a business. For the study, the researcher has purposively selected 100 micro enterprises. The findings shows that the most of the parameters of competencies of the managers of the micro enterprises are rated very high. The parameters book-keeping/accounting and tax planning are rated high and moderate competencies to run a business.